Prognostic utility of somatosensory evoked potentials in supratentorial hemorrhage-induced prolonged disorders of consciousness - Hui Feng; Yongli Wu; Yuqing Han; Fangyu Chen; Huiyue Feng; Juanjuan Fu (European Journal of Medical Research)
Abstract Purpose To evaluate the prognostic value of somatosensory evoked potentials (SEPs) in predicting functional outcomes in patients with prolonged disorders of consciousness (PDOC) secondary to severe supratentorial intracerebral hemorrhage (ICH). Methods From August 2023 to August 2024, 77 patients with PDOC secondary to supratentorial intracerebral hemorrhage were prospectively enrolled from Critical Care Rehabilitation Department of Nanjing Jiangning Hospital. Within one week of enrollment, all patients were assessed using the Chinese Coma Recovery Scale-Revised (CRS-R) score, short-latency somatosensory evoked potentials (SLSEPs), and middle-latency somatosensory evoked potentials (MLSEPs). Patients were followed for 6 months, with outcomes classified using the Extended Glasgow Outcome Scale (GOSE). Based on GOSE scores, patients were categorized into good outcome groups (GOSE score ≥ 4) and poor outcome groups(GOSE score < 4). Results A total of 77 PDOC patients were included in the study. After 6 months of follow-up, 44 patients (57.14%) demonstrated good outcomes, while 33 (42.86%) had poor outcomes. The absence of N20 and N60 potentials showed significant differences between outcome groups (P < 0.05). Multivariate logistic regression analysis revealed that baseline CRS-R score (OR = 1.51, P = 0.009), N20-P25 mean amplitude (OR = 6.58, P = 0.003), and P45-N60 mean amplitude (OR = 11.99, P = 0.02) were significant predictors of good outcomes in all patients. In the minimally conscious state (MCS) subgroup, the CRS-R score at baseline (OR = 1.38), N20-P25 mean amplitude (OR = 1.85), and P45-N60 mean amplitude (OR = 16.01) significantly predicted outcomes; receiver operating characteristic analysis demonstrated that both N20-P25 mean amplitude (AUC = 0.82, cutoff 1.55 μV, sensitivity = 86.4%, specificity = 69.0%) and P45-N60 mean amplitude (AUC = 0.70, cutoff 0.43 μV, sensitivity = 79.1%, specificity = 71.4%) effectively predicted good outcomes (GOSE ≥ 4) in all patients. Notably, in the MCS subgroup, P45-N60 mean amplitude showed exceptional predictive performance (AUC = 0.93, cutoff 0.38 μV), with 88.6% sensitivity and 100% specificity. Pearson correlation analysis indicated that N20-P25 mean amplitudes significantly correlated with CRS-R score improvement after 6 months (P < 0.05) in all patients and the MCS subgroup. The P45-N60 mean amplitude showed a significant correlation with CRS-R score improvement only in the MCS subgroup (P < 0.05). Conclusion Quantitative analysis of SEPs offers clinically significant prognostic value in PDOC following supratentorial ICH. Notably, MLSEPs' demonstrate particularly precise predictive capabilities for MCS patients.